Effect of ultrasound treatment, oil addition and storage time on lycopene stability and in vitro bioaccessibility of tomato pulp. (1st April 2015) - Anese, Monica; Bot, Francesca; Panozzo, Agnese; Mirolo, Giorgio; Lippe, Giovanna
Highlights: Ultrasound treatment caused a permanent viscosity increase of tomato pulp. Ultrasonication of tomato pulp slightly affected lycopene in vitro bioaccessibility. Sunflower oil incorporation to tomato pulp decreased lycopene bioaccessibility. Upon storage lycopene bioaccessibility of tomato pulps with or without oil decreased. Abstract: This study was performed to investigate the influence of ultrasound processing on tomato pulp containing no sunflower oil, or increasing amounts (i.e. 2.5%, 5% and 10%), on lycopene concentration and in vitro bioaccessibility at time zero and during storage at 5 °C. Results confirmed previous findings in that ultrasonication was responsible for cell breakage and subsequent lycopene release in a highly viscous matrix. Neither the ultrasound process nor oil addition affected lycopene concentration. A decrease of approximately 35% lycopene content occurred at storage times longer than 15 days, due to isomerisation and oxidation reactions. No differences in lycopene in vitro bioaccessibility were found between the untreated and ultrasonically treated samples; this parameter decreased as a consequence of oil addition. Losses of lycopene in vitro bioaccessibility ranging between 50% and 80% occurred in the untreated and ultrasonically treated tomato pulps with and without oil during storage, mainly due to carotenoid degradation.